An assessment of the effectiveness and perception of the doodle - Video reinforced teaching method - Anita Teli; Sheetal Harkuni; Deepti M Kadeangadi; Madhumati Patil (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Today, doodle videos are employed as a teaching tool in contemporary education, and they are known to aid in the development of attention and likelihood of increase in the memory. Feedback is a systematic ongoing review process to evaluate and improvise the teaching methodology to ensure its effectiveness. AIMS AND OBJECTIVE: The aim of this study was to evaluate the impact of newer teaching method compared to traditional method and assess the student's perception on the same. METHODOLOGY: This is a nonrandomized experimental study, wherein a doodle video on the topic of "Parkinson's disease" was designed and displayed to the students through the link generated. The knowledge acquisition was evaluated using a comprehensive multiple-choice question test for both groups, and another structured questionnaire on the perceptions of newer teaching method was assessed. RESULTS/OBSERVATION: There was a statistically significant difference (P < 0.03) for the mean assessment scores between the groups. A total of 80 responses were obtained for feedback assessment on perception of newer method for five closed-ended questions, and 54 responses were obtained for one open-ended question. Thematic analysis was performed for open-ended questions. CONCLUSION: Student's performance was better with doodle video teaching. Doodle video was considered an innovative method of teaching by students; it helped them understand better. The feedback taken offered an opportunity to understand the student's perspective and their teaching needs.